Reconfigurable reflectarray antenna: background, classification and configurable mechanisms - Siti Fatimah Harun; Mohd Fais Mansor (Penerbit Universiti Kebangsaan Malaysia, 2023)
Reflectarray antennas have emerged as one of the most suitable choice for 5G network base station antennas due to their ability to combine the advantages of parabolic reflectors and phased array antennas. These antennas offer a lightweight structure, high gain, and low impedance mismatch losses. High gain and low loss are crucial factors in ensuring the antenna delivers low latency and high-quality 5G radio signals. The application of 5G technology becomes more practical and efficient with the capability to adjust the functionality of a single 5G antenna or enable reconfiguration. This reconfigurable technique simplifies the multi-antenna systems and significantly reduces costs, making it more practical and systematic. Furthermore, this reconfigurability is particularly beneficial for satellite applications, as it allows for the reconfiguration of the signal in the event of satellite movement on the space. This paper aims to discuss the historical development of reconfigurable reflectarray antennas, focusing on the innovations in each configurable mechanism. The paper further explores the classification of configurations employed by this antenna, encompassing frequency configuration, radiation pattern, polarization, and hybrid configurations that integrate multiple existing configuration classifications. Finally, the research paper provides a discussion of the most recent research and innovations in the configurable mechanisms of reflectarray antennas.